Use the function rule f(x)= x * (-1)^x. Find the output of f(2)

A. 4
B. 3
C. -2
D. 2

1 answer

If your question means:

x • ( - 1 )ˣ

Then replace x with 2

2 • ( - 1 )²

Since ( - 1 )² = 1

f(2) = 2 • ( - 1 )² = 2 • 1 = 2
Similar Questions
    1. answers icon 15 answers
    1. answers icon 12 answers
  1. use the function rule f(X) =3x-2 find the output f(1.5).A: 2.5 B: -2.5 C: 6.5 D: - 6.5 I Guess A. Please help!
    1. answers icon 9 answers
    1. answers icon 48 answers
more similar questions